The determinants of the performance in the entrance exam of the Federal University of Minas Gerais (Avaliação: Revista da Avaliação da Educação Superior, 2024)
In order to decrease inequalities in tertiary education attendance, many Brazilian public institutions implemented affirmative action policies in the last decades. In particular, a bonus policy was implemented at UFMG in 2009, which was substituted by a quota policy in 2012. Besides, other policies also implemented by this and other public universities in Brazil may have had an indirect effect of promoting an increase in minorities’ attendance, such as the Restructuring and Expansion of Federal Universities (Reuni) policy and the use of the National Exam of the Secondary Level (ENEM) as a tool for tertiary education student’s selection. This paper analyzes the determinants of the performance in the entrance exam of Federal University of Minas Gerais (UFMG), between the years of 2009 and 2013, with a focus on these policy changes. Affirmative action and Reuni policies did not affect remarkably the performance of minorities at the UFMG´s selection process. However, the use of ENEM as the first stage in this process relatively decreased the performance of minorities. Moreover, differences for skin color were dwarfed by other inequalities, such as the household income, the parent’s educational level or the type of the secondary school attended by the student.